2016
DOI: 10.1080/09515089.2016.1225194
|View full text |Cite
|
Sign up to set email alerts
|

Is there really an omission effect?

Abstract: The omission effect, first described by Spranca et al. (1991), has been extensively studied in the proceeding decades and repeatedly confirmed (Cushman et al., 2012)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 21 publications
(28 reference statements)
1
11
0
Order By: Relevance
“…Spranca et al (1991) suggested that people's actions were judged as having stronger causal links to the outcome compared with inactions. Follow-up studies supported this idea (Henne et al, 2019;Kordes-de & Vaal, 1996;Willemsen & Reuter, 2016) with action being perceived as more intentional than inaction (Hayashi, 2015;Jamison et al, 2020;Kordes-de Vaal, 1996). A related explanation is about the role of information.…”
Section: Scopementioning
confidence: 91%
See 1 more Smart Citation
“…Spranca et al (1991) suggested that people's actions were judged as having stronger causal links to the outcome compared with inactions. Follow-up studies supported this idea (Henne et al, 2019;Kordes-de & Vaal, 1996;Willemsen & Reuter, 2016) with action being perceived as more intentional than inaction (Hayashi, 2015;Jamison et al, 2020;Kordes-de Vaal, 1996). A related explanation is about the role of information.…”
Section: Scopementioning
confidence: 91%
“…Theories, Mechanisms, Explanations, and Hypotheses Spranca et al (1991) were among the first to discuss possible explanations for the omission bias. The causal relevance hypothesis focuses on the different causal attributions in omission and commission (Willemsen & Reuter, 2016). Spranca et al (1991) suggested that people's actions were judged as having stronger causal links to the outcome compared with inactions.…”
Section: Scopementioning
confidence: 99%
“…Generally, the action effect refers to a phenomenon whereby, across a range of scenarios, people judge that agents who perform an action played a greater role in causing the outcome than agents who did nothing at all (Cushman & Young, 2011;Walsh & Sloman, 2011;Willemsen & Reuter, 2016; for a review, see Feldman & Yay, 2018). Many researchers have found this difference in causal judgment (Cushman & Young, 2011;Walsh & Sloman, 2011), and some have explored and suggested potential moderators (Willemsen & Reuter, 2016).…”
Section: Explaining the Action Effectmentioning
confidence: 99%
“…In this case, it seems less reasonable to claim that you received the free sample because you did not change your subscription status. In what we will refer to as the action effect for causal judgment, people consistently judge that actions like these are more causal than inactions (Cushman & Young, 2011;Feldman & Yay, 2018;Spranca, Minsk, & Baron, 1991;Walsh & Sloman, 2011;Willemsen & Reuter, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Second, norms can also be injunctive (Alicke, 1992;Knobe & Fraser, 2008;Kominsky, Phillips, Gerstenberg, Lagnado, & Knobe, 2015;Reuter, Kirfel, van Riel, & Barlassina, 2014;Sytsma et al, 2012;Willemsen & Reuter, 2016). Injunctive norms include both prescriptive norms, which tell people what they should do, and proscriptive norms, telling people what they should not do.…”
Section: Norms and Their Effects On Causal Judgementsmentioning
confidence: 99%